Concurrent Aerobic Plus Resistance Exercise Versus Aerobic Exercise Alone to Improve Health Outcomes in Paediatric Obesity: A Systematic Review and Meta-Analysis - Garcia-Hermoso, A (BMJ Publishing Group, 2018)
Objective To determine if the combination of aerobic and resistance exercise is superior to aerobic exercise alone for the health of obese children and adolescents. Design Systematic review with meta-Analysis. Data sources Computerised search of 3 databases (MEDLINE, EMBASE, and Cochrane Controlled Trials Registry). Eligibility criteria for selecting studies Studies that compared the effect of supervised concurrent exercise versus aerobic exercise interventions, with anthropometric and metabolic outcomes in paediatric obesity (6-18â €..years old). The mean differences (MD) of the parameters from preintervention to postintervention between groups were pooled using a random-effects model. Results 12 trials with 555 youths were included in the meta-Analysis. Compared with aerobic exercise alone, concurrent exercise resulted in greater reductions in body mass (MD=â 2.28â €..kg), fat mass (MD=â 3.49%; and MD=â 4.34â €..kg) and low-density lipoprotein cholesterol (MD=â 10.20â €..mg/dL); as well as greater increases in lean body mass (MD=2.20â €..kg) and adiponectin level (MD=2.59â €..μg/mL). Differences were larger for longer term programmes (>24â €..weeks). Summary Concurrent aerobic plus resistance exercise improves body composition, metabolic profiles, and inflammatory state in the obese paediatric population. Trial registration number CRD42016039807. © Published by the BMJ Publishing Group Limited. For permission to use (where not already granted under a licence) please go to http://www.bmj.com/company/products-services/rights-And-licensing/.